Screening of phytochemicals from the ethanolic extracts of Gnetum gnemon, Gnetum latifolium and Cynometra malaccensis of Kuala Keniam, Pahang - Ahmat, N; Kamarozaman, A S; Johari, M S M; Abas, F; Mohamad, S A S; Yunoh, S M M (IOP Publishing, 2022)
The diversity of plants has led to various findings in the medicinal world. The abundance of bioactive compounds existing in the plant is the main factor contributing to its application in pharmaceutical industries. Gnetum gnemon, Gnetum latifolium and Cynometra malaccensis were collected from the forest area, Stesen Penyelidikan UiTM-Perhilitan, Kuala Keniam, Taman Negara, Pahang. This project focussed on profiling the bioactive constituent through phytochemical screening via Shinoda, Mayer, saponin, tannin, and terpenoid tests from the ethanolic extract of stem bark, stem, leaves and twigs of the three species. The results displayed that all plant parts showed the presence of flavonoids, terpenes and tannins. These compounds might contribute to the good properties of the plants.